2014
DOI: 10.3109/10428194.2014.953150
|View full text |Cite
|
Sign up to set email alerts
|

Expression of indoleamine 2,3-dioxygenase in leukemic cells indicates an unfavorable prognosis in acute myeloid leukemia patients with intermediate-risk cytogenetics

Abstract: The immunomodulatory effects of indoleamine 2,3-dioxygenase (IDO) are ascribed to its ability to catalyze breakdown of the essential amino acid L-tryptophan. We applied reverse transcription-polymerase chain reaction (RT-PCR) to examine IDO mRNA expression in acute myeloid leukemia (AML) blasts, and investigated its clinical significance. We enrolled 62 patients with AML between April 2005 and March 2013. Bone marrow-derived mononuclear fractions were separated and extracted mRNA was amplified by PCR. RT-PCR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…This would suggest that in vivo MDSCs cells account for most IDO1 expression in LyP. Our findings on these cell lines agree with gene expression profiling data 27 (see Table S3 of ref. 26 for more details), where IDO1 was not ranked among the top 400 differentially expressed genes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This would suggest that in vivo MDSCs cells account for most IDO1 expression in LyP. Our findings on these cell lines agree with gene expression profiling data 27 (see Table S3 of ref. 26 for more details), where IDO1 was not ranked among the top 400 differentially expressed genes.…”
Section: Discussionsupporting
confidence: 90%
“…We report, for the first time, that several cell types other than malignant cells contribute to the expression of IDO1 in CTCL. Among hematologic malignancies, IDO1 expression has been previously found in the acute myeloid leukemia (AML) blasts 26 and in MDSCs in chronic lymphocytic leukemia (CLL) of B-cell origin 10 . We found the spectrum of IDO1-expressing cells to differ markedly among CTCL subtypes.…”
Section: Discussionmentioning
confidence: 74%
“…70) as well as IDO1 (REF. 71). In a separate study, the leukaemic cells from 12 of 15 patients with AML were found to suppress T cell proliferation in vitro by secreting arginase II, an enzyme that actively converts arginine into urea.…”
Section: Neoantigens and The Immune Responsementioning
confidence: 99%
“…IDO is also produced by cancer cells; therefore, Trp metabolism helps tumors evade the host immune responses and provides survival advantages to tumors [11]. Many studies have shown that a high level of IDO expression in tumors is a poor prognostic factor [13,14], and it is thought that IDO expression induces Trp deficiency in cancer patients.…”
Section: Introductionmentioning
confidence: 99%